Ранневизантийские архитектурные детали из Херсонеса - Буйских, А.В. (Материалы по археологии, истории и этнографии Таврии, 2003)
Буквально в последнее десятилетие отечественная историография обогатилась целым рядом специальных исследований, охватывающих различные аспекты истории и культуры Херсонеса в 1V-V вв. Это позволило значительно откорректировать современные представления о политических, культурных, а также этничеа»1х процессах, происходивших в Юго-Западной Таврике и приведших в результате к образованию одного из крупнейших форпостов Византийской империи в Черноморском бассейне. Architectural finds, few in number architectural details - capital of columns and pilasters dating to the end of the 3rd - 5th centuries, are examined in this article. All of them belong to Corinth order and are presented as the produce of local stone-cutting shops and import. It is significant that the capitals of columns are cut from limestone, capital of pilasters are only marble ones. All the examined architectural details testify to the fact that during the transition period from antiquity to the Middle Ages in Chersonesos they continued to erect public buildings where architectural order was observed. The character of those buildings is unknown. Mediterranean and Balkan analogies to the capitals from Chersonesos enable us to suppose that all those buildings were not used for living. The small size of the details points to the fact that they were a part of interior decoration. Stylistically, these order details continued the antique traditions of the development of Corinth order representing its later period.